Keystroke Dynamic Authentication Using Combined MHR (Mean of Horner’s Rules) and Standard Deviation - Didih Rizki Chandranegara; Fauzi Dwi Setiawan Sumadi (Kinetik: Game Technology, Information System, Computer Network, Computing, Electronics, and Control, 2019)
Keystroke Dynamic Authentication used a behavior to authenticate the user and one of biometric authentication. The behavior used a typing speed a character on the keyboard and every user had a unique behavior in typing. To improve classification between user and attacker of Keystroke Dynamic Authentication in this research, we proposed a combination of MHR (Mean of Horner’s Rules) and standard deviation. The results of this research showed that our proposed method gave a high accuracy (93.872%) than the previous method (75.388% and 75.156%). This research gave an opportunity to implemented in real login system because our method gave the best results with False Acceptance Rate (FAR) is 0.113. The user can be used as a simple password and ignore a worrying about an account hacking in the system.